2021
DOI: 10.1007/s11892-021-01378-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy for Critical Limb Ischemia: Advantages, Limitations, and New Perspectives for Treatment of Patients with Critical Diabetic Vasculopathy

Abstract: Purpose of Review To provide a highlight of the current state of cell therapy for the treatment of critical limb ischemia in patients with diabetes. Recent Findings The global incidence of diabetes is constantly growing with consequent challenges for healthcare systems worldwide. In the UK only, NHS costs attributed to diabetic complications, such as peripheral vascular disease, amputation, blindness, renal failure, and stroke, average £10 billion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 145 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…The molecular mechanisms of new vessel growth may be related to the ability of the injected PB-MNCs to induce vascular remodeling, by paracrine activity (delivering growth factors, cytokines, angiogenic coding, and non-coding RNAs, either free or encapsulated in EVs of small size-exosomes, to soft tissue), as has been suggested by the results in preclinical studies [ 27 29 ]. Of note, in line with this hypothesis, we here observed that patients with higher tissue perfusion at the end of the follow-up were characterized by a higher number of small-size EVs.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of new vessel growth may be related to the ability of the injected PB-MNCs to induce vascular remodeling, by paracrine activity (delivering growth factors, cytokines, angiogenic coding, and non-coding RNAs, either free or encapsulated in EVs of small size-exosomes, to soft tissue), as has been suggested by the results in preclinical studies [ 27 29 ]. Of note, in line with this hypothesis, we here observed that patients with higher tissue perfusion at the end of the follow-up were characterized by a higher number of small-size EVs.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of ED is different between type 1 DM (T1DM) from T2DM. Indeed, while the insurgence of ED in T1DM is mainly triggered by hyperglycemia alone, in T2DM also insulin resistance and circulating fatty acids play a role (52,72). Considering the effects of hyperglycemia on the endothelium at the molecular level, one of the first steps towards the development of ED is represented by the inhibition of the enzyme glyceraldehyde 3-phosphate dehydrogenase.…”
Section: Nrf2 Activity In the Context Of Diabetic Cardiovascular Comp...mentioning
confidence: 99%
“…17−23 Using exosomes for CLI treatment is superior to growth factor and miRNA therapies since vascularization and muscle regeneration simultaneously require multiple factors, and these can be provided by exosomes but not readily by delivery systems for growth factors and miRNAs. 24 While stem cell-derived exosomes have shown encouraging therapeutic effects for ischemic limbs without diabetes, 17−23,25−27 the efficacy of current exosome therapy for diabetic ischemic limbs is not most favorable. 24 Current exosomes are not tailored with an optimal composition of proangiogenic and promyogenic factors for accelerated vascularization and myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…24 While stem cell-derived exosomes have shown encouraging therapeutic effects for ischemic limbs without diabetes, 17−23,25−27 the efficacy of current exosome therapy for diabetic ischemic limbs is not most favorable. 24 Current exosomes are not tailored with an optimal composition of proangiogenic and promyogenic factors for accelerated vascularization and myogenesis. While exosomes can be engineered to contain exogenous cargos necessary for these processes, current approaches typically use soluble biochemicals and growth factors, which may complicate both the exosome composition as well as the resulting therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%